The Effect of Iron Overload on Erythrocyte Histological Composition, Insulin-like Growth Factor, and Liver Function in Beta Thalassemia Patients - Haneen G. Faisal; Khulood N. Rasheed; Mousa M. Marbut (Journal of Population Therapeutics and Clinical Pharmacology, 2022)
This study is conducted in the College of Sciences / Department of Biology- University of Tikrit, in cooperation with the Thalassemia Center in Erbil Governorate, for the period from December 2021 - June 2022 to investigate the effect of iron overload on the histological composition of red blood cells and some physiological markers in beta thalassemia patients. A number of 120 individuals participated in this study, including 20 healthy individuals representing the control group of both sexes (11 males and 9 females) and 100 individual with beta thalassemia major who were undergoing treatment of both sexes (56 males and 44 females). Their average ages range between (3-36) years, and all disease cases have been diagnosed by specialized physicians. The results indicate through the colored blood slides that red blood cells appear generally hypochromic microcytic, as well as a discrepancy in the size and shape of red blood cells. Some of these red blood cells are large in size (macrocytosis), some in the form of a teardrop (ovalocyte), and others are target or stomatal or ghostly. It is also shown that there are significant differences in the shapes, sizes, and stains of RBCs in the blood smears of pathological cases (thalassemia) compared to the control group, but not significant when comparing males with females, except for the target cell, which has shown differences in this respect. As for the results of the analyzes of the chemical parameters GPT, GOT, ALP, the results show a significant increase in the activity of GOT, GPT and ALP enzyme in patients with beta thalassemia major compared to the control group, while there is a significant decrease in the level of IGF-1 concentration in patients with beta thalassemia major compared to the control group.